2018
DOI: 10.21815/jde.018.141
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Silver Diamine Fluoride in U.S. Dental Schools’ Predoctoral Curricula

Abstract: Silver diamine fluoride (SDF), a low‐cost topical agent used in many countries to arrest dental caries, was cleared as a desensitizing agent by the Food & Drug Administration for the U.S. market in 2014. The aim of this study was to survey U.S. dental schools regarding their teaching of SDF. Email invitations were sent to all accredited U.S. predoctoral dental education programs (n=66) in September 2016. Deans, chairs, and selected faculty members were asked to respond or forward the survey‐link provided to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
(23 reference statements)
0
15
1
Order By: Relevance
“…8 Also, it was cleared as a desensitizing agent by the Food and Drug Administration for the US market in 2014. 9 According to Mellberg et al, fluoride introduced into the oral cavity gets cleared with passage of time; hence, a continuous supply of fluoride is essential for anticaries effect. 10 Enamel fluoride content was seen to increase significantly even after 6 months of application of SDF compared to fluoride varnish and APF gel.…”
Section: Introductionmentioning
confidence: 99%
“…8 Also, it was cleared as a desensitizing agent by the Food and Drug Administration for the US market in 2014. 9 According to Mellberg et al, fluoride introduced into the oral cavity gets cleared with passage of time; hence, a continuous supply of fluoride is essential for anticaries effect. 10 Enamel fluoride content was seen to increase significantly even after 6 months of application of SDF compared to fluoride varnish and APF gel.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was reported that even among schools that contain SDF in their curriculum, not all faculty were aware of SDF being taught which creates an incongruent learning environment for dental students. 28 The same study also showed that the amount of time devoted to teaching SDF varies between schools: of the 42 schools that had SDF in their curriculum, 32.5% taught the material for <1 hour, 37.5% for 1-2 hours, and 25% for 3-5 hours. 28 These variations in time may be the reason for the inconsistent knowledge and perception of SDF among dental students from different schools which was captured in our results.…”
Section: Discussionmentioning
confidence: 91%
“…The inconsistency can be attributed to the fact that SDF is relatively new in the United States, as well as to the factors previously discussed that affected the implementation of SDF into clinical use such as the off‐label use and lack of universal guidelines. Additionally, it was reported that even among schools that contain SDF in their curriculum, not all faculty were aware of SDF being taught which creates an incongruent learning environment for dental students 28 . The same study also showed that the amount of time devoted to teaching SDF varies between schools: of the 42 schools that had SDF in their curriculum, 32.5% taught the material for <1 hour, 37.5% for 1‐2 hours, and 25% for 3‐5 hours 28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations